Analysis Of Sugar Marketing Strategy In Terms Of Increasing The Revenue Of Pt. Plantation Nusantara Xiv (Persero) - Zulham Anugrah Kasim; Abd Rahman Kadir; Mursalim Nohong (SEIKO : Journal of Management & Business, 2023)
The study aims to describe the sugar-marketing strategy used by the company to increase its income; to analyze the marketing mix factors (product, price, promotion and distribution network) which may have an influence on the sale of sugar of the company and to determine the most influential factors of marketing mix that affect the sale of sugar of the company. The study was carried out in PT. Nusantara Plantation XIV (Persero). The population are 40 direct buyer customers of the company consisting of 27 wholesalers and 13 retailers. thesamples are selected by saturated sampling method (census). The data are analyzed using SWOT and multiple linear regression analyses. The study indicates that the new strategy usable by the company to increase its revenue is an aggressive strategy by which the companyutilizes its internal strength to make use of the great opportunity. The marketing mix variables, product, price, promotion and distribution network, simultaneously have a significant influence on the sugar sale to increase the revenue of the company and the most dominant influence of the marketing mix variables on the sale of sugar are price, product, distribution network and respective promotions Keywords: marketing mix, SWOT Analysis